Struktur Komunitas Fitoplankton Di Ekosistem Padang Lamun Alami dan Buatan Di Perairan Teluk Awur Jepara - Agus, ELza Lusia; Widianingsih, Widianingsih; Riniatsih, Ita (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Phytoplankton is an autotrophic microorganism lived on water as primer producer. Its existence is important for the other marine organisms. This research aims to now the abundance, diversity, uniformity, dominant and community similarity of phytoplankton area at natural and artificial seagrass bed ecosystem, Teluk Awur Jepara Waters. This research was carried aut every 2 weeks started from July 7th till September 2th 2012 at natural and artificial seagrass bed of Teluk Awur Jepara waters. Phytoplankton sample was collected from Teluk Awur Jepara seagrass bed whereas the method used is explorative with case study approach. Data was collected using sample survey method while location is determined by purposive method. The research found 3 classes of phytoplankton, consisted of 31 genera. Bacillariophyceae, Cyanophyceae and Dinophyceae. ). The most abundance of phytoplankton was found in the 4th sampling at station IV (195,17 cell/l) and the lowest abundance was found in 2nd sampling at station IV (63,49 cell/l). Diversity index ranged at 1,74 – 3,25 or medium category. Uniformity index ranged at 0,49 – 0,71 or medium category. Dominant index ranged at 0,07 – 0,51 or low category. Community similarity index ranged at 57,14 -100,00% or high category.